Financial Transaction Prevention Mechanism Suspicious By Notary - Nikita Mikail Akbar (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2019)
This research is to analyze the mechanism of the notary in avoiding Suspicious Financial Transaction to the deed he made. Researchers use the statutory approach and conceptual approach in normative research. Based on the research that has been done, the notary mechanism in avoiding suspicious financial transactions by applying the principle of recognizing service users with procedures through the identification of Service Users, verification of Service Users; and monitoring of User Transactions. The principle of recognizing service users for notaries required by the PPATK and the Minister of Law and Human Rights basically synergizes and is not too different from the introduction of service users conducted by a notary public before the application of the obligation to recognize service users is regulated in Minister of Law and Human Rights Regulation Number 9 of 2017. Keywords: Notary; Suspicious Financial Transactions; Recognizing Service Users